Revisiting the charge compensation mechanisms in LiNi0.8Co0.2−yAlyO2 systems. Issue 10 (23rd July 2019) - Lebens-Higgins, Zachary W.; Faenza, Nicholas V.; Radin, Maxwell D.; Liu, Hao; Sallis, Shawn; Rana, Jatinkumar; Vinckeviciute, Julija; Reeves, Philip J.; Zuba, Mateusz J.; Badway, Fadwa; Pereira, Nathalie; Chapman, Karena W.; et al.
Abstract : The emergence of oxidized oxygen RIXS features at high voltages for Ni-rich layered oxide cathodes. Abstract : Oxygen participation, arising from increased transition metal–oxygen covalency during delithiation, is considered essential for the description of charge compensation in conventional layered oxides. The advent of high-resolution mapping of the O K-edge resonant inelastic X-ray scattering (RIXS) provides an opportunity to revisit the onset and extent of oxygen participation. Combining RIXS with an array of structural and electronic probes for the family of Ni-rich LiNi0.8 Co0.2− y Al y O2 cathodes, we identify common charge compensation regimes that are assigned to formal transition metal redox (<4.25 V) and oxygen participation through covalency (>4.25 V). From O K-edge RIXS maps, we find the emergence of a sharp RIXS feature in these systems when approaching full delithiation, which has previously been associated with lattice oxidized oxygen in alkali-rich systems. The lack of transition metal redox signatures and strong covalency at these high degrees of delithiation suggest this RIXS feature is similarly attributed to lattice oxygen charge compensation as in the alkali-rich systems. The RIXS feature's evolution with state of charge in conventional layered oxides is evidence that this feature reflects the depopulation of occupied O 2p states associated with oxygen participation.